2010
DOI: 10.1007/s12011-009-8587-3
|View full text |Cite
|
Sign up to set email alerts
|

Properties Evaluation of a New MRI Contrast Agent Based on Gd-Loaded Nanoparticles

Abstract: Nanosized materials of gadolinium oxide can provide high-contrast enhancement in magnetic resonance imaging (MRI). The aim of this research was to characterize a novel emulsion composed of a silicon-based nanocomposite polymer (NCP) and gadolinium (III) oxide (Gd₂O₃) nanoparticles. The size and morphological structure of this nanoparticle are determined by particle size analysis device (zeta sizer) and transmission electronic microscope. We determined composition of Gd₂O₃ nanoparticles with energy dispersive X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The excess of Gd ions and agglomerated nanoparticle in the solution was eliminated by 1000MW membrane (Dialysis tubing, benzoylated, Sigma, USA) for 24h and of 12000MW membrane (Dialysis tubing cellulose membrane, Sigma, USA) for 24h across idolized water. [7,8,9] GD-DEG-DG: 5mg ml -1 0f DEG-Gd2O3 was washed sequentially with 10 ml each of DI water, THF-DI water and finally with anhydrous THF for several repeated washes to eliminate any remaning traces of water. carbonyldiimidazole (CDI) was then added into the suspension at a concentration of 50 mg ml -1 and reacted at 700rpm mixing in a shaker for 2h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The excess of Gd ions and agglomerated nanoparticle in the solution was eliminated by 1000MW membrane (Dialysis tubing, benzoylated, Sigma, USA) for 24h and of 12000MW membrane (Dialysis tubing cellulose membrane, Sigma, USA) for 24h across idolized water. [7,8,9] GD-DEG-DG: 5mg ml -1 0f DEG-Gd2O3 was washed sequentially with 10 ml each of DI water, THF-DI water and finally with anhydrous THF for several repeated washes to eliminate any remaning traces of water. carbonyldiimidazole (CDI) was then added into the suspension at a concentration of 50 mg ml -1 and reacted at 700rpm mixing in a shaker for 2h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…After cooling, the nanocrystals formed were separated and purified from agglomerations or large-size particles by centrifuge filtration for 30 min at 40°C and 2,000 rpm (filters: polyethersulfone, 0.2 μm, Vivascience Sartorius, Hannover, Germany). Free Gd 3+ ions and excess DEG in the solution were eliminated by 1,000 MW membrane (dialysis tubing, benzoylated, Sigma-Aldrich, USA) for 24 h and by 12,000 MW membrane (dialysis tubing cellulose membrane, Sigma-Aldrich, USA) for 24 h across deionized water, which these sections were not included in our previous study [13]. …”
Section: Methodsmentioning
confidence: 99%
“…As a new surface covering material, this group in a previous study reported some of the primary magnetic properties of diethyleneglycol (DEG) in combination with Gd oxide-based nanoparticles [10]. However, still further researches on the matters of the synthesis procedure, effective size, and agglomeration of gadolinium nanoparticles coated with DEG materials are needed to be done [11-13]. On the other hand, polyethylene glycol (PEG), due to its considerable physicochemical properties, has an especial interest as covering of nanoparticle surfaces [13-17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, since Gd +3 ions have an unpaired electrons and is highly toxic, it must be coated by some suitable biocompatible chelators such as Diethylenetriaminpentaasetic acid (DTPA) [2]. Magnetic resonance imaging (MRI) is a noninvasive imaging technique capable of obtaining high-resolution anatomical images of the body.…”
Section: Introductionmentioning
confidence: 99%